2017
DOI: 10.1080/15476286.2017.1358348
|View full text |Cite
|
Sign up to set email alerts
|

Codon adaptation to tRNAs with Inosine modification at position 34 is widespread among Eukaryotes and present in two Bacterial phyla

Abstract: The modification of adenosine to inosine at position 34 of tRNA anticodons has a profound impact upon codon-anticodon recognition. In bacteria, I34 is thought to exist only in tRNA, while in eukaryotes the modification is present in eight different tRNAs. In eukaryotes, the widespread use of I34 strongly influenced the evolution of genomes in terms of tRNA gene abundance and codon usage. In humans, codon usage indicates that I34 modified tRNAs are preferred for the translation of highly repetitive coding seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 32 publications
(54 reference statements)
1
56
0
Order By: Relevance
“…In multicellular organisms, A to I editing has been observed in both messenger RNA (mRNA) and tRNA. In bacteria however, only one editing site was discovered in tRNA Arg2 , but never in mRNA (Rafels-Ybern, Torres, Grau-Bove, Ruiz-Trillo, & Ribas de Pouplana, 2018). I generated in the tRNA anticodon is known to pair with U, C, or A in mRNA during translation.…”
Section: Discussionmentioning
confidence: 99%
“…In multicellular organisms, A to I editing has been observed in both messenger RNA (mRNA) and tRNA. In bacteria however, only one editing site was discovered in tRNA Arg2 , but never in mRNA (Rafels-Ybern, Torres, Grau-Bove, Ruiz-Trillo, & Ribas de Pouplana, 2018). I generated in the tRNA anticodon is known to pair with U, C, or A in mRNA during translation.…”
Section: Discussionmentioning
confidence: 99%
“…Complementation of codons and anticodons could be achieved through tRNA modification, with adenosine at the wobble position of the tRNA being converted to inosine. Rafels-Ybern et al. (2017) recently showed that the deamination of this adenosine is widespread amongst eukaryotes and that codons complementary to deaminated tRNA molecules are enriched in highly expressed genes.…”
Section: Discussionmentioning
confidence: 99%
“…The wide-scale deamination of adenosine to inosine is common across different RNA types in Metazoa ( Porath et al. 2017 ) and Rafels-Ybern et al. (2017) showed that metazoan and plant genomes possess a greater concentration of codons translated by modified tRNAs than the genomes of unicellular eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…We previously suggested that ADAT might be controlling specific genetic programs [45]. Therefore, the BRCA1-driven negative regulation of ADAT2 may silence specific genetic programs the codon usage of which makes their translation dependent on tRNAs with I34 [46]. Emerging evidence indicates that tRNA expression and tRNA repertoire are modulated during tumorigenesis [47,48].…”
Section: Discussionmentioning
confidence: 99%